High char yields of DOPO/organosilicon-modified epoxy resins and phosphorus–silicon synergism of thermal stability. (September 2019) - Luo, Jiemin; Li, Rui; Zou, Huawei; Chen, Yang; Liang, Mei
The phosphorus/silicon-modified epoxy resin (ED231) was prepared via a two-step reaction process. Firstly, the 9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO)-modified epoxy was synthesized by ring-opening reaction between DOPO and epoxy resin of diglycidyl ether of bisphenol A (E51). Afterward, the organic silicone intermediate (SY231) was grafted onto the DOPO-modified epoxy to obtain the ED231 product. The thermal stability and thermal–mechanical properties of ED231 systems were characterized by thermogravimetric analysis (TGA) and dynamic mechanical thermal analysis, respectively. TGA results indicated that the phosphorus/silicon-modified epoxy resin (ED231) exhibited high char yields. For example, the solid residue for ED231-40 (5 phr DOPO and 40 phr SY231) at 800°C increased from 16.77% for the pure epoxy resin to 36.25% under nitrogen atmosphere and from 0% to 14.29% under air atmosphere, respectively. Scanning electron microscopy observations suggested that the ED231 systems could form an intact and continuous char layer which could significantly improve the thermal properties.